Determinants Of Intentions To Use Mobile Banking With The Technology Acceptance Model (Tam) Approach - Siregar, Tima Sari; Nasution, Hamni Fadlilah; Fauzan, M; Matondang, Zulaika (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
AbstractMany students have difficulty using mobile banking. The existence of mobile banking should make it easier for students to transact and give students freedom of time, quick response, and cost savings. The purpose of this study is to determine the influence perceived usefulness and perceived ease of use on the intention to use Mobile banking. The concept in this study uses the Technology Acceptance Model (TAM). This model is a theoretical tool to test the extent to which a technology is accepted and benefited by a user. This type of research is quantitative research. The data collection technique uses questionnaires, documentation with a sample of 68 respondents. The data analysis technique used is using SmartPLS software version 4. Measurement models are used for validity and reliability tests, while structural models are used for causality tests (hypothesis testing with predictive models). The results of the study showed that there was an influence of usability perception on the intention to use mobile banking. And there is an influence of the perception of ease of use on the Intention to Use Mobile banking. In addition, the perception of usability and perceived ease of use explained the intention to use mobile banking by 0.902 or 90.2% and the rest was explained by other variables that were not studied by the researchers.